Clinical Features Associated with Female Genital Mutilation/Cutting: A Pilot Longitudinal Study - Paslakis, Georgios; Farré, Josep M; Tolosa-Sola, Iris; Palazón-Llecha, Alba; Domínguez-Cagnon, Helena; Jiménez, María; Martínez Rosselló, Berta; Barri-Soldevila, Pere; Mestre-Bach, Gemma (Journal of Clinical Medicine, 2021)
(1) Background: Female genital mutilation/cutting (FGM/C) is associated with physical and psychological complications. However, there is scarce literature on how women with FGM/C respond to treatment interventions. (2) Methods: In the present pilot longitudinal study, we assessed changes in general psychopathology (Symptom Check List-90-R), sexual functioning and distress (Female Sexual Function Index, Female Sexual Distress Scale-Revised, and Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) female sexual dysfunction criteria), body image (Body Shape Questionnaire), and sexual body image (Female Genital Self-Image Scale) in a sample ofn= 15 women with FGM/C before and after reconstructive surgery. (3) Results: Sexual distress was significantly improved following surgery. We also observed an improvement in general psychopathology and genital self-image. However, sexual function was not improved. (4) Conclusions: These results provide evidence for the benefits of reconstructive surgery on sexual distress in women with FGM/C. The impact of surgery on sexual function cannot be conclusively evaluated.
Keywords: female genital mutilation/cutting; body image; genital self-image; female sexual function; psychopathology; clitoral reconstruction; JCR; Scopus